Relationship Between Interleukin 8 Levels And Body Mass Index In Patients With Endometrial Cancer - Halimputera, Vincentius Julio; Pelupessy, Nugraha Utama; Mailoa, Johnsen; Hamid, Firdaus; Arifuddin, Sharvianty; Rahman, Abdul (Journal of Neonatal Surgery, 2025)
Introduction: Increased body mass index (BMI) is one of the risk factors for endometriosis cancer associated with chronic inflammatory processes that can be confirmed by increased inflammatory markers in obese patients such as interleukin 8 (IL-8). This study aims to evaluate the relationship between IL-8 levels to body mass index and clinicopathological characteristics of patients with endometrial carcinoma. Methods: This was cross-sectional study that conducted from November 2022 to February 2023 in Endometrial Cancer. Demographic and clinicopathological data were collected. BMI and IL-8 serum were measured. Data were analyzed with SPSS 27.0, using the Mann-Whitney test, Kruskal Wallis test and Spearman correlation test. Results: Lymphovascular Space Invasion (LVSI) and stage were not significantly associated with IL-8 levels (p>0.05). IL-8 levels were higher in obese patients than in non-obese patients but not statistically significant (p>0.05). Endometrial carcinoma type was significantly associated with IL-8 levels (p<0.05). Higher age was significantly associated with higher IL-8 levels (p<0.05). Conclusion: Obesity was not correlated to IL-8 levels in endometrial carcinoma patients, but IL-8 levels are influenced by age and type of endometrial carcinoma.